White matter injury in stroke and CNS disease - Carmichael, S. Thomas; Matute, Carlos; Xi, Guohua; Zhang, John H.; Baltan, Selva (Springer Series in Translational Stroke Research, 2014)
The first book to provide a systematic expert summary of normal white matter morphology as well as white matter injury following stroke and other CNS injuries. White matter injury can result from both ischemic and hemorrhagic stroke as well as a host of other CNS diseases and conditions such as neonatal injuries, neurodegenerative disorders including Alzheimer's disease, traumatic brain injuries, carbon monoxide poisoning, and drug or alcohol overdoses. The extent of white matter injury is extremely important to patient outcomes. Several recent technological developments including advanced neuroimaging and the breeding of new rodent models of white matter injury have provided growing insight into initial damage and repair after a stroke or other damaging event.